Pengaruh Nilai Kerja, Kecerdasan Emosional dan Work Life Balance Terhadap Komitmen Karir (Studi Kasus Pada Generasi Y Kota Semarang) - Iqbal Baihaqi; Rudi Suryo Kristanto (ECONBANK: Journal of Economics and Banking, 2020)
The phenomenon that occurs in the field states that almost half of the workers surveyed reached 49% of people who said workers had made a drastic change in career or work field. This study aims to determine the effect of work value, emotional intelligence, and work life balance on career commitment. The population in this study is generation Y in the city of Semarang. Non-probability sampling techniques were used to determine the research sample and data collection was carried out by distributing questionnaires to 150 respondents. In this study, the method used is multiple linear regression. From the analysis, it was found that emotional intelligence has an effect on career commitment. Meanwhile, work value and work life balance do not affect career commitment. The value of Adjusted R2 is 0.475, which means that 47.5% of the variation in Career Commitment can be explained by the value of work, emotional intelligence, and work life balance, while the remaining 52.5% of career commitment can be explained by other factors